The impact of transformation process on the quality of service in the Vhembe Health District, Limpopo Province - Madzivhandila, Mushavhani Wilson (My University, 2006)
Refer to document
Thesis (MPA.) -- University of Limpopo, 2006
Keywords: Transformation process; Service delivery; Transformation; Social change